EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN SAINTIFIK PADA MATERI BILANGAN DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS VII SMP NEGERI SE-KABUPATEN BOYOLALI - Adiningsih, Sri; Usodo, Budi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from studentâs AQ. The learning models compared were TPS with scientific approach, NHT with scientific approach, and classical with scientific approach. The type of the research was a quasi-experimental research. The population were all students of Junior High School in Boyolali. The samples are the students of SMPN 1 Boyolali, SMPN 1 Sawit and SMPN 3 Sawit, which taken by using stratified cluster random sampling technique. The instruments used were mathematics achievement test and AQ questionnaire. The data was analyzed using unbalanced two-ways Anova. The conclusions were as follows. (1) TPS with scientific approach gives better mathematics achievement than NHT with scientific approach, and both gives better mathematics achievement than classical with scientific approach. (2) Climbers students have better mathematics achievement than campers and quitters students,Â  campers students have better mathematics achievement than quitters students. (3) For TPS with scientific approach, climbers students have better mathematics achievement than campers and quitters students. Campers and quitters students have the same mathematics achievement. For NHT and classical with scientific approach, climbers students have better mathematics achievement than quitters students. Climbers and campers students have the same mathematics achievement. Campers and quitters students have the same mathematics achievement. (4) For climbers students, TPS with scientific approach and NHT with scientific approach give the same mathematics achievement. NHT with scientific approach and classical with scientific approach give the same mathematics achievement. TPS with scientific approach gives the better mathematics achievement than classical with scientific approach. For campers and quitters students, all learning models give the same mathematics achievement.Keywords: TGT, NHT, Classical, Scientific Approach, AQ.